2021
DOI: 10.1371/journal.pone.0258893
|View full text |Cite
|
Sign up to set email alerts
|

Surviving SARS and living through COVID-19: Healthcare worker mental health outcomes and insights for coping

Abstract: Objective Explore how previous work during the 2003 Severe Acute Respiratory Syndrome (SARS) outbreak affects the psychological response of clinical and non-clinical healthcare workers (HCWs) to the current COVID-19 pandemic. Methods A cross-sectional, multi-centered hospital online survey of HCWs in the Greater Toronto Area, Canada. Mental health outcomes of HCWs who worked during the COVID-19 pandemic and the SARS outbreak were assessed using Impact of Events—Revised scale (IES-R), Generalized Anxiety Diso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 30 publications
0
16
0
2
Order By: Relevance
“…Interestingly, one factor which led to no significant differences in job enjoyment, satisfaction outside work, wellbeing, resilience and redeployment-related anxiety, was the staff 's type of role: e.g., patient vs. non-patient facing occupational role during the pandemic. While this seems counterintuitive as most of the previous research suggested that increased exposure to COVID-19 pandemic decreases psychological wellbeing (5,7,9,10,18,27), there have been a number of studies showing nonclinical staff to have lower wellbeing scores than HCWs (17, 31,42,58). The authors suggested that the unbalanced degrees of preparation for and support through the pandemic, could be a possible explanation for the low wellbeing scores reported by staff not directly involved in managing the pandemic.…”
Section: Discussionmentioning
confidence: 95%
“…Interestingly, one factor which led to no significant differences in job enjoyment, satisfaction outside work, wellbeing, resilience and redeployment-related anxiety, was the staff 's type of role: e.g., patient vs. non-patient facing occupational role during the pandemic. While this seems counterintuitive as most of the previous research suggested that increased exposure to COVID-19 pandemic decreases psychological wellbeing (5,7,9,10,18,27), there have been a number of studies showing nonclinical staff to have lower wellbeing scores than HCWs (17, 31,42,58). The authors suggested that the unbalanced degrees of preparation for and support through the pandemic, could be a possible explanation for the low wellbeing scores reported by staff not directly involved in managing the pandemic.…”
Section: Discussionmentioning
confidence: 95%
“…Previous research has shown that the COVID-19 pandemic had a significant psychological toll on HCWs [ 5 , 6 , 7 , 8 , 9 , 10 , 11 ], including the development of Post-Traumatic Stress symptoms [ 12 , 13 ]. Specific subgroups within HCWs, such as front-line and female workers, were particularly vulnerable to worse mental health outcomes [ 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to the current COVID-19 pandemic, UHN cared for the most acutely unwell SARS patients. The SARS pandemic was notable for the distress it generated amongst healthcare workers, with significant levels of depression, anxiety, insomnia and post-traumatic distress reported (R. Maunder, 2004 ; R. Maunder et al, 2006 ; Styra et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%